Modelos de negócios em coworkings : uma análise a partir da dinâmica de criação, configuração e apropriação de valor - Reis, Alessandro Paes dos (2019)
Despite the exponential growth in the number of coworkings in the world, it is estimated that 60% of these businesses are not profitable, thus demonstrating an error in the creation, configuration and appropriation of value in this sector. On the other hand, there is an absence of academic work on coworkings business models. Therefore, the question that arises in this dissertation is: how are coworkings business models developed? It is interpreted that the understanding of the business model in coworkings requires a perspective of dynamic and emergent strategy, based on a process of trial and error. From the methodological point of view, one opted for the analysis of narratives, in which the synthesis results from the confrontation between thesis and antithesis. From the identification of the events, the focal actors and the understanding of the implicit and explicit oppositions (dilemmas) and syllogisms (conclusion of the dilemmas) in the speech and actions of the interviewees, it was possible to identify the main learning. As a result, it is noted that coworkings structure their business models facing the dilemmas of creating value through the identification of the ideal point x restriction of financial resources, private spaces x open space, understanding of needs x value proposition, competitor's price x financial need of the entrepreneur, lack of experience in coworking x experience of the entrepreneur, the exploitation of space for space rent x space of entrepreneurship and the dilemma of rental x use of the building itself. Regarding the configuration of value, the main dilemmas identified were energy allocated in the sale of space x concession of spaces for strategic partners, the decision on the use of own software x third-party software, analysis and decision on own investment x third-party investment, approaches to creating an engaged community through the dissemination of events and messages via whatsapp / email x conversations with coworkers and the use of a formal x informal code of conduct. Regarding the appropriation of value, the main dilemmas reported were the use of traditional methods of customer capture x social networks / digital marketing, the profitability of physical spaces x other forms of profitability and the discussion of maintaining the expansion x balance the accounts due to the option to use equity and withdrawals from closed contracts. All this analysis is carried out through a constant discussion of dilemmas and contradictions (oppositions) inherent to the decision-making process (actions, syllogisms) and consequent ruptures in the execution of activities.